The X window system and motif : - Newmarch, J. D. (Addison-Wesley Pub., 1992)
How little do you need to know to work in the X environment and to write Xlib programs? Providing a rapid overview rather than an in-depth treatment, the book covers a useful subset of X, and through exercises explores more.